Relationships between use of harmony control, acculturation, and subjective well-being among Asians in the United States. - Yamanaka, Momi. (My University, 2004)
A convenient sample of (N = 233) Asians who were living in U.S. completed at least a portion of the survey. Use of harmony control was not a good predictor of Asians' either positive or negative well-being after controlling for the negative impact of discrimination experience. Identification with Asian culture, measured by SL-ASIA, had a statistically significant relationship with one of 5 harmony control subscales.

Harmony control is a new type of control introduced by Morling and Fiske (1999) and brought a new explanation for people's perceivably unmotivated behaviors. In this web-based study, Asians' use of harmony control and it relationship with the acculturation level measured by the Suinn-Lew Asian Self Identity Acculturation Scale (SL-ASIA) and well-being (using 5 well-being measurements) were examined.
Keywords: Psychology, Clinical.; Education, Guidance and Counseling.; Control (Psychology); Education, Bilingual and Multicultural.; Psychological tests.; Acculturation Research.